2018
DOI: 10.20944/preprints201808.0271.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioplastic Polyhydroxyalkanoate (PHA): Recent Advances in Modification and Medical Applications

Abstract: A wide variety of bacteria are found to be the tiny factories in the production of polyhydroxyalkanoate (PHA) biopolymer. PHA is the polyesters of 3-hydroxyalkanoic acids which occur in bacteria when the bacteria is subjected to nutrient limitation and simultaneously fed with an excess amount of carbon. This unfavorable condition forces the bacteria to store carbon in the form of resorbable cellular inclusions called PHA. Biosynthesized PHA has the ability to replace the currently feasible harmful petroleum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 170 publications
(226 reference statements)
0
6
0
Order By: Relevance
“…These composites consist on a polymeric matrix in which wood (or whatever lignocellulosic subproduct of the food industry or agroforestry) particles (from 10 to 60 wt %, depending on the manufacturing process) are embedded, leading to an appearance and surface finishing similar to natural wood. As many times, the lignocellulosic fillers are by-products from other sectors, they are cheap and do not increase the cost of the WPC; in addition, they come from natural resources and, subsequently, they represent a sustainable source for use in new and environmentally friendly materials [3][4][5]. These WPCs are already replacing the use of traditional woods in some applications, which is an important protection of forest resources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These composites consist on a polymeric matrix in which wood (or whatever lignocellulosic subproduct of the food industry or agroforestry) particles (from 10 to 60 wt %, depending on the manufacturing process) are embedded, leading to an appearance and surface finishing similar to natural wood. As many times, the lignocellulosic fillers are by-products from other sectors, they are cheap and do not increase the cost of the WPC; in addition, they come from natural resources and, subsequently, they represent a sustainable source for use in new and environmentally friendly materials [3][4][5]. These WPCs are already replacing the use of traditional woods in some applications, which is an important protection of forest resources.…”
Section: Introductionmentioning
confidence: 99%
“…These WPCs are already replacing the use of traditional woods in some applications, which is an important protection of forest resources. WPCs formulations have been optimized in sectors as important as automotive, outdoor furniture, interior design, railings, floors, coatings, decks, fences, pergolas, decking, and so on [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal plasticizer needs to be biodegradable, nontoxic, and stable or nonvolatile [ 33 ]. Examples of common plasticizers are glycerol (considered as a conventional type of plasticizer for hydrophilic polymers [ 33 ], oxypropylated glycerin (or laprol), glycerol triacetate, polyethylene glycol, 4-nonylphenol, acetyl tributyl citrate, acetylsalicylic acid ester, salicylic ester, dioctyl phthalate, and dibutyl phthalate [ 49 ]. Behind the crystallinity and low cost, their physical and thermal properties are also of extreme importance.…”
Section: Polyhydroxyalkanoates (Phas) In Microalgaementioning
confidence: 99%
“…It has been reported that the degradation rate of P(3HB) in P(3HB)/lignin blends can be reduced due to the formation of strong hydrogen bonds between lignin and P(3HB) [ 53 ]. The degradation rates of some immiscible binary blends such as P(3HB)/poly(propiolactone), P(3HB)/poly(ethylene adipate), and P(3HB)/P(3HB-co-3HV) were found to be higher than those of their pure counterparts due to their phase-separated structure [ 49 ].…”
Section: Polyhydroxyalkanoates (Phas) In Microalgaementioning
confidence: 99%